PENGGUNAAN BAHASA INDONESIA PADA PAPAN NAMA BADAN PUBLIK DI GORONTALO - Sri Nurlaela Sabubu (TELAGA BAHASA, 2021)
The use of Indonesian is an obligatory on signboard of building as a mandate in Undang-Undang Republik Indonesia Number 24 of 2009 concerning Bendera, Bahasa, dan Lambang Negara serta Lagu Kebangsaan (the Flag, Language and State Emblem and National Anthem). The purpose of this study was to find out how the Indonesian language is used on the signboards of public offices in Gorontalo. The method used is descriptive qualitative. The results showed that there were 27 spelling errors in the use of Indonesian on the signboards of public offices in Gorontalo City, in the form of errors in writing punctuation marks, abbreviations, and foreign words.Keywords: signboard; public offices; spelling errors